Analgesic effect of external oblique intercostal block in laparoscopic cholecystectomy: A retrospective study - Yi, Shuai; Li, Dan; Zhang, Xin-lei; Duan, Fen-yu; Gao, Han; Kong, Ming-jian (Open medicine (Warsaw, Poland), 2024)
The aim of this study was to assess the impact of the external oblique intercostal block (EOIB) on early postoperative pain in patients who underwent laparoscopic cholecystectomy. 120 patients were divided into two groups: the EOIB group (Group E) and the control group (Group C). The assessed variables were mainly intraoperative remifentanil usage, numerical rating scale (NRS) pain scores at 0, 1, 2, 4, 6, 12, and 24 h postoperatively, cumulative fentanyl consumption within 24 h postoperatively and within the first-hour post-anesthesia care unit. Remifentanil consumption during surgery was significantly reduced in Group E compared to Group C. Postoperative fentanyl requirements were also lower in Group E at 1 and 24 h after surgery. Furthermore, Group E demonstrated significantly lower NRS scores at 0, 1, 2, 4, and 6 h postoperatively and a reduced need for rescue analgesia compared to Group C. However, at 12 h post-surgery, Group E's NRS scores were slightly higher than Group C's. The EOIB is associated with reduced pain within the first 24 postoperative hours following laparoscopic cholecystectomy.